Method for preparing silicon-aluminum aerogel from fly ash

Through the reaction of fly ash with aqueous sodium hydroxide solution and CO2, combined with the drying control agent of formamide and dimethylformamide, the staged drying process was prepared to prepare a silicon-aluminum aerogel with low thermal conductivity and high specific surface area, which solved the problem of The problems of expensive raw materials and complex processes have achieved the resource utilization of fly ash and the preparation of high-value-added products.

CN119160922APending Publication Date: 2024-12-20CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310727974.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the existing aerogel preparation methods, the raw material price is high and the process is cumbersome, and the economic benefits of fly ash as solid waste are low, so it fails to effectively utilize its resource value.

Method used

Fly ash and sodium hydroxide aqueous solution were used for alkali-soluble reaction, and CO2 was then introduced for acidification and decomposition. Formide and dimethylformamide were added as drying control agents. After aging, solvent replacement and segmented drying, silicon was prepared. Aluminum aerogel.

Benefits of technology

Resource utilization of fly ash is realized, and aerogel products with low thermal conductivity and high specific surface area are prepared, which improves economic benefits and optimizes process simplification and low energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160922A_ABST
    Figure CN119160922A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing silicon-aluminum aerogel from fly ash, and belongs to the technical field of solid waste resource utilization. The method comprises the following steps: S1, mixing fly ash and a sodium hydroxide aqueous solution according to a mass ratio of 1: 3-1: 8, carrying out an alkali dissolution reaction, and carrying out solid-liquid separation to obtain a silicon-aluminum mixed solution; s2, introducing CO2 into the silicon-aluminum mixed solution until the pH value is 8.0-10.0, so as to obtain a silicon-aluminum mixed colloid; s3, adding a drying control agent into the silicon-aluminum mixed colloid, and then stirring and standing to obtain silicon-aluminum wet gel; the drying control agent is a mixture of formamide and dimethylformamide, and the mass ratio of the formamide to the dimethylformamide is (1: 3)-(1: 10); and S4, carrying out aging, solvent replacement and segmented drying on the silicon-aluminum wet gel to obtain the silicon-aluminum aerogel. The aerogel prepared by the invention has the advantages of high specific surface area, low density, mesoporous structure and low heat-conducting property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid waste resource utilization, and specifically relates to a method for preparing silicon-aluminum aerogel from fly ash. Background Art

[0002] Aerogel is a gel material, which is a porous material with a three-dimensional network structure. Aerogel has the characteristics of low density, high porosity, high specific surface area, and low thermal conductivity. Therefore, it has a wide range of applications and can be used in aerospace, building energy conservation, catalysis, optical materials, etc.

[0003] At present, there are many methods for preparing aerogel. For example, Chinese patent application document CN101244825A discloses a method for preparing silica aerogel using diatomaceous earth as raw material. Specifically, an alkaline solution is mixed with diatomaceous earth for reaction at a reaction temperature of 10-150°C for a reaction time of 0.5-10 hours. After the reaction, solid-liquid separation is performed, and the liquid phase is taken and the pH value is adjusted to 4-12 with an acid to form a sol, which is then allowed to stand to form a gel. The gel is subjected to solvent replacement and then dried to obtain silica aerogel.

[0004] Chinese patent application document CN102066252B discloses a colloidal silica particle and a method for producing the same, as well as an organic solvent-dispersed silica sol, a polymerizable compound-dispersed silica sol, and a dicarboxylic acid glycoside-dispersed silica sol of the particle, wherein the colloidal silica particle is a colloidal silica particle having an average content of at least one polyvalent metal element M selected from iron, aluminum, zinc, zirconium, titanium, tin, and lead of 0.001 to 0.02 in terms of M / Si molar ratio, and an average primary particle size of the colloidal silica particle of 5 to 40 nm, wherein the content of the polyvalent metal element M present in the outermost layer of the colloidal particle is 100% per 1 nm. 2 The surface area of ​​the colloidal particles is 0 to 0.003. When the colloidal silica particles in this embodiment are dispersed in an organic compound, the solid acid on the surface of the colloidal silica particles will not cause dispersion and coloring of the organic compound.

[0005] Chinese patent document CN112573527B discloses a method for preparing ultra-high purity silica sol by hydrolysis of elemental silicon, ultra-high purity silica sol and application. In this method, guanidine compounds are used as catalysts to prepare initial silica sol by reacting high-purity silicon powder with water, and then ultra-high purity silica sol with a mass fraction of more than 20% and a particle size of 20-100nm is obtained through a series of steps such as filtering and removing impurities, catalyst impurities, water replacement and concentration. The metal ion content in the silica sol is less than 1ppm.

[0006] Chinese patent document CN111218024B discloses a method for continuously preparing core-shell hydrophilic-phobic bipolar composite aerogel powder, wherein a hydrophilic alkoxide silicon compound, a hydrophobic alkyl-substituted alkoxide silicon compound, and an organic mixed solvent are mixed to form a mixed solution; an acid catalyst is added to the mixed solution for a condensation reaction, and a dispersing solvent is added during the condensation reaction and stirred, so that the mixed solution undergoes phase separation and gelation during the stirring process to form core-shell hydrophilic-phobic bipolar aerogel particles, and core-shell hydrophilic-phobic bipolar aerogel powder can be obtained after filtering and drying, thereby improving the overall preparation speed of core-shell hydrophilic-phobic bipolar aerogel particles and powder, improving the post-processing mixing efficiency, and improving the thermal insulation effect of the product.

[0007] In the above-mentioned aerogel preparation method, the raw materials used are expensive and the preparation process is complicated. Therefore, it is necessary to find suitable synthetic raw materials. Fly ash is the main solid waste discharged from coal-fired power plants. Its main oxide components are SiO2, Al2O3, FeO, Fe2O3, CaO, TiO2, etc. The fly ash emissions are huge, so it will cause great pressure on the environment. At present, its main disposal methods are landfill or as building materials, and the economic benefits are low. Therefore, if fly ash is used as a raw material to synthesize aerogel, it will turn waste into treasure and produce greater economic benefits. Summary of the invention

[0008] In order to solve the above problems existing in the prior art, the present invention provides a method for preparing silicon-aluminum aerogel from fly ash. The preparation method of the present invention can not only improve the benefits of comprehensive utilization of fly ash, but also the prepared silicon-aluminum aerogel has low thermal conductivity and high specific surface area.

[0009] An object of the present invention is to provide a method for preparing silicon-alumina aerogel from fly ash, the method comprising the following steps:

[0010] S1, mixing fly ash and sodium hydroxide aqueous solution in a mass ratio of 1:3-1:8, performing an alkali dissolution reaction, and obtaining a silicon-aluminum mixed solution through solid-liquid separation;

[0011] S2, introducing CO2 into the silicon-aluminum mixed solution until the pH value is 8.0-10.0, performing an acidification decomposition reaction, and obtaining a silicon-aluminum mixed colloid;

[0012] S3, adding a drying control agent to the silica-alumina mixed colloid, and then stirring and standing to obtain a silica-alumina wet gel; the drying control agent is a mixture of formamide and dimethylformamide, and the mass ratio of the formamide to the dimethylformamide is 1:3 to 1:10;

[0013] S4. A silica-alumina aerogel is obtained by aging, solvent replacement and segmented drying the silica-alumina wet gel.

[0014] In the present invention, solid waste fly ash is used as raw material, after alkali dissolution reaction and acidification decomposition reaction, a drying control agent is added to obtain a silicon-aluminum wet gel, and then an aerogel is obtained after aging, solvent replacement and segmented drying. Among them, in step S2, CO2 is introduced into the solution at a suitable flow rate until the pH of the system is 8.0-10.0. The inventors found that the silicon-aluminum mixed colloid obtained under this condition has better stability; in step S3, formamide and dimethylformamide are controlled within a certain ratio range, and through the synergistic effect of the two, it is beneficial to obtain an aerogel with low thermal conductivity.

[0015] Through the method of the present invention, on the one hand, the resource utilization of solid waste fly ash is realized; at the same time, an aerogel product with low thermal conductivity and high specific surface area is obtained.

[0016] In some embodiments, in step S1, the mass fraction of the sodium hydroxide aqueous solution is 15% to 30%.

[0017] In the present invention, the inventors have found that the mass concentration of the sodium hydroxide aqueous solution has a great influence on the alkaline dissolution reaction. If the concentration is too low, the reaction will be incomplete and the reaction efficiency will be low; if the concentration is too high, sodium silicate will easily form on the surface of the fly ash, affecting subsequent reactions.

[0018] In some embodiments, in step S1, the reaction temperature of the alkaline dissolution reaction is 60°C to 150°C, and the reaction time is 30 min to 180 min.

[0019] In the present invention, the reaction conditions required for the alkaline dissolution reaction are mild and the energy consumption is low.

[0020] In some embodiments, in step S2, the CO2 is introduced at a rate of 10 ml / min to 100 ml / min.

[0021] In some embodiments, in step S3, the amount of the drying control agent added is 10% to 30% of the volume of the silica-alumina mixed colloid.

[0022] In the present invention, the addition amount of the drying control agent is within a suitable range, which is conducive to obtaining an aerogel with a low thermal conductivity and a high specific surface area; the inventors have found that if the addition amount is too low, the reaction is incomplete and the thermal conductivity of the obtained aerogel is high; if the addition amount is too high, it is easy to cause the pores of the aerogel to collapse, resulting in a decrease in the specific surface area of ​​the aerogel.

[0023] In some embodiments, in step S4, the aging time is 6 to 48 hours, and the aging temperature is 20°C to 50°C.

[0024] In the present invention, the strength of the gel skeleton is enhanced through aging, thereby reducing the shrinkage of the gel in the subsequent drying process, resulting in a reduction in specific surface area.

[0025] In some embodiments, in step S4, during the solvent replacement process, the replacement temperature is 20°C to 60°C, and the replacement time is preferably 4 to 10 hours.

[0026] In some embodiments, the solvent used for the solvent replacement is one or more of deionized water, ethanol, isopropanol, acetone, and n-hexane.

[0027] In some embodiments, the volume ratio of the solvent used for the solvent replacement to the wet silica-alumina gel is 1:1 to 20:1, and the number of replacements is preferably 3 to 7 times.

[0028] In the present invention, in order to allow the liquid as the dispersion medium in the voids of the formed wet gel network structure to be fully replaced by the replacement solvent, the replacement frequency is preferably 3 to 7 times.

[0029] In some embodiments, in step S4, the staged drying includes four stages of drying with a gradually increasing drying temperature within a range of 20° C. to 180° C.;

[0030] In some preferred embodiments, the drying conditions of the four-stage drying include: the temperature of the first stage drying is 20°C to 40°C, and the drying time is 12 to 48 hours; the temperature of the second stage drying is 40°C to 80°C, and the drying time is 6 to 12 hours; the temperature of the third stage drying is 80°C to 120°C, and the drying time is 2 to 4 hours; the temperature of the fourth stage drying is 120°C to 180°C, and the drying time is 0.5 to 2 hours.

[0031] In the present invention, the wet gel is dried by gradually increasing the temperature, which can maintain the complete skeleton structure of the gel and prevent deformation and shrinkage.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention uses solid waste fly ash as raw material to prepare aerogel, realizing the resource utilization of solid waste fly ash; at the same time, a high value-added aerogel product is obtained, and the obtained aerogel has a high specific surface area, low density, a mesoporous structure and low thermal conductivity. In some embodiments, the specific surface area of ​​the aerogel prepared by the method of the present invention exceeds 500m 2 / g, density less than 0.1g / cm 3 The average pore size is about 5 to 20 nm, and the thermal conductivity is less than 0.05 W / m·k, which has excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1The present invention is a flow chart of a method for preparing silicon-alumina aerogel from fly ash in one embodiment of the present invention. DETAILED DESCRIPTION

[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The experimental methods without specific conditions in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used are all available from commercial channels unless otherwise specified.

[0037] Example 1

[0038] The method for preparing silicon-aluminum aerogel from fly ash comprises the following steps:

[0039] S1. Weigh 100g of fly ash (wherein the SiO2 content is 52wt%, the Al2O3 content is 35wt%, and the fly ash comes from a power plant in Jungar Banner, Inner Mongolia), mix the fly ash with a 15% sodium hydroxide aqueous solution at a solid-liquid mass ratio of 1:3, and heat to 60°C for alkaline dissolution reaction for 30min. After the reaction is completed, solid-liquid separation is performed to obtain a silicon-aluminum mixed solution, in which the contents of Al2O3 and SiO2 are 3.6g / L and 16g / L, respectively;

[0040] S2, introducing CO2 into the silicon-aluminum mixed solution at a rate of 10 ml / min, so that the mixed solution is acidified and decomposed to obtain a silicon-aluminum mixed colloid, with a pH end point of 8.0;

[0041] S3, adding a mixture of formamide and dimethylformamide in a mass ratio of 1:3 as a drying control agent to the silica-alumina mixed colloid, the addition ratio of the drying control agent being 10% of the volume of the colloid, stirring, and standing to obtain a silica-alumina wet gel;

[0042] S4. The silica-alumina wet gel is aged for 48 hours at a temperature of 50°C. After the aging, the wet gel is subjected to solvent replacement, wherein the replacement solvent is deionized water and ethanol, wherein the volume ratio of water to ethanol is 1:1, the volume ratio of the replacement solvent to the wet gel is 5:1, the replacement temperature is 20°C, the replacement time is 10 hours, and the replacement times are 3 times; then ethanol is used for replacement, wherein the volume ratio of the replacement solvent to the wet gel is 5:1, the replacement temperature is 20°C, the replacement time is 10 hours, and the replacement times are 4 times; the replaced gel is dried in sections, wherein the first drying temperature is 20°C, the drying time is 48 hours, then the temperature is raised to 40°C for the second drying, the drying time is 12 hours, the temperature is continued to be raised to 80°C for the third drying, the drying time is 4 hours, the temperature is continued to be raised to 120°C for the fourth drying, the drying time is 2 hours, and the silica-alumina aerogel is obtained.

[0043] Example 2

[0044] The method for preparing silicon-aluminum aerogel from fly ash comprises the following steps:

[0045] S1. Weigh 100g of fly ash (wherein the SiO2 content is 41wt%, the Al2O3 content is 45wt%, and the fly ash comes from a power plant in Jungar Banner, Inner Mongolia), mix the fly ash with a 22% sodium hydroxide aqueous solution at a solid-liquid mass ratio of 1:5, and heat to 100°C for alkaline dissolution reaction for 100min. After the reaction is completed, solid-liquid separation is performed to obtain a silicon-aluminum mixed solution, in which the contents of Al2O3 and SiO2 are 7.6g / L and 34.4g / L, respectively.

[0046] S2, introducing CO2 into the silicon-aluminum mixed solution at a rate of 60 ml / min, so that the mixed solution is acidified and decomposed to obtain a silicon-aluminum mixed colloid, and the pH end point is 9.0;

[0047] S3, adding a mixture of formamide and dimethylformamide in a mass ratio of 1:7 as a drying control agent to the silica-alumina mixed colloid, the addition ratio of the drying control agent is 20% of the volume of the colloid, stirring, and standing to obtain a silica-alumina wet gel;

[0048] S4. The silica-alumina wet gel is aged for 30 hours at a temperature of 35°C. After the aging, the wet gel is subjected to solvent replacement, wherein the replacement solvent is deionized water and ethanol, wherein the volume ratio of water to ethanol is 1:1, the volume ratio of the replacement solvent to the wet gel is 5:1, the replacement temperature is 40°C, the replacement time is 7 hours, and the replacement times are 3 times; then ethanol is used for replacement, wherein the volume ratio of the replacement solvent to the wet gel is 5:1, the replacement temperature is 40°C, the replacement time is 7 hours, and the replacement times are 4 times; the replaced gel is dried in sections, wherein the first drying temperature is 30°C, the drying time is 30 hours, then the temperature is raised to 60°C for the second drying, the drying time is 9 hours, the temperature is continued to be raised to 100°C for the third drying, the drying time is 3 hours, the temperature is continued to be raised to 150°C for the fourth drying, the drying time is 1 hour, and silica-alumina aerogel is obtained.

[0049] Example 3

[0050] The method for preparing silicon-aluminum aerogel from fly ash comprises the following steps:

[0051] S1. Weigh 100g of fly ash (wherein the SiO2 content is 37wt%, the Al2O3 content is 48wt%, and the fly ash comes from a power plant in Jungar Banner, Inner Mongolia), mix the fly ash with a 30% sodium hydroxide aqueous solution at a solid-liquid mass ratio of 1:8, and heat to 150°C for alkaline dissolution reaction for 180min. After the reaction is completed, solid-liquid separation is performed to obtain a silicon-aluminum mixed solution, in which the contents of Al2O3 and SiO2 are 10.2g / L and 42g / L, respectively;

[0052] S2, introducing CO2 into the silicon-aluminum mixed solution at a rate of 100 ml / min, so that the mixed solution is acidified and decomposed to obtain a silicon-aluminum mixed colloid, and the pH end point is 10.0;

[0053] S3, adding a mixture of formamide and dimethylformamide in a mass ratio of 1:10 as a drying control agent to the silica-alumina mixed colloid, the addition ratio of the drying control agent being 30% of the volume of the colloid, stirring, and standing to obtain a silica-alumina wet gel;

[0054] S4, aging the wet silica-alumina gel, the aging time is 6h, the aging temperature is 20℃, after the aging, the wet gel is subjected to solvent replacement, the replacement solvent is deionized water and isopropanol, wherein the volume ratio of water to isopropanol is 1:1, the volume ratio of the replacement solvent to the wet gel is 5:1, the replacement temperature is 60℃, the replacement time is 4h, and the replacement times are 3 times; then ethanol and isopropanol are used for replacement, wherein the volume ratio of ethanol to isopropanol is 1:1, the volume ratio of the replacement solvent to the wet gel is 5:1, the replacement temperature is 60℃, the replacement time is 10h, and the replacement times are 2 times; the replaced gel is dried in sections, the first drying temperature is 40℃, the drying time is 12h, then the temperature is raised to 80℃ for the second drying, the drying time is 6h, the temperature is continued to be raised to 120℃ for the third drying, drying for 2h, and the temperature is continued to be raised to 180℃ for the fourth drying, drying for 0.5h, to obtain silica-alumina aerogel.

[0055] Comparative Example 1

[0056] The method for preparing silica-alumina aerogel from fly ash is basically the same as that in Example 3, except that in step S1, the mass fraction of the sodium hydroxide aqueous solution is 10%.

[0057] Comparative Example 2

[0058] The method for preparing silica-alumina aerogel from fly ash is basically the same as that in Example 3, except that in step S1, the mass fraction of the sodium hydroxide aqueous solution is 40%.

[0059] Comparative Example 3

[0060] The method for preparing silica-alumina aerogel from fly ash is basically the same as that in Example 3, except that in step S2, the pH end point is controlled to be 5.0.

[0061] Comparative Example 4

[0062] The method for preparing silica-alumina aerogel from fly ash is basically the same as that in Example 3, except that in step S3, the drying control agent is formamide.

[0063] Comparative Example 5

[0064] The method for preparing silica-alumina aerogel from fly ash is basically the same as that in Example 3, except that in step S3, the drying control agent is dimethylformamide.

[0065] Comparative Example 6

[0066] The method for preparing silica-alumina aerogel from fly ash is basically the same as that in Example 3, except that in step S4, no segmented drying is performed, but the aerogel is directly dried at 100° C. for 6 h.

[0067] Performance Testing

[0068] The performance of the silica-alumina aerogels prepared in Examples 1-3 and Comparative Examples 1-6 was tested, and the results are shown in Table 1 below:

[0069] The testing methods for specific surface area, density, average pore size and thermal conductivity are conventional methods and will not be described in detail here.

[0070] Table 1 Silica-alumina aerogel performance test results

[0071]

[0072] It can be seen from the data in the table that the specific surface area of ​​the silica-alumina aerogels prepared in Examples 1-3 is relatively large, exceeding 500 m 2 / g, density less than 0.1g / cm 3 , the average pore size is about 5 to 20 nm, the thermal conductivity is less than 0.05 W / m·k, and it has low thermal conductivity. In Comparative Examples 1 and 2, the mass fraction of the sodium hydroxide aqueous solution used is not within the scope of the present invention; in Comparative Example 3, the pH endpoint is controlled to be 5.0; in Comparative Examples 4 and 5, only one of dimethylformamide and formamide is added as the drying control agent. The results show that the specific surface area of ​​the obtained silica-alumina aerogel is significantly reduced, the density is too large, the pore size is significantly increased, the thermal conductivity is significantly increased, and the performance is significantly reduced. In Comparative Example 6, no segmented drying is performed, but it is directly dried at 100°C for 6 hours. The results show that the specific surface area of ​​the obtained silica-alumina aerogel is greatly reduced, the density is too large, the pore size is greatly increased, the thermal conductivity is greatly increased, and the performance is greatly reduced. The results show that by controlling the mass fraction of sodium hydroxide aqueous solution, controlling the pH value of the reaction system, using a specific drying control agent (a combination of formamide and dimethylformamide) and performing staged drying, silica-alumina aerogels with high specific surface area, low density, small pore size and low thermal conductivity can be obtained.

[0073] The above embodiments are only specific implementation methods of the present invention, which are used to illustrate the technical solutions of the present invention rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the aforementioned embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be covered within the protection scope of the present invention.

Claims

1. A method for preparing silicon-alumina aerogel from fly ash, characterized in that: The steps include: S1, mixing fly ash and sodium hydroxide aqueous solution in a mass ratio of 1:3-1:8, performing an alkali dissolution reaction, and obtaining a silicon-aluminum mixed solution through solid-liquid separation; S2, introducing CO2 into the silicon-aluminum mixed solution until the pH value is 8.0-10.0, to obtain a silicon-aluminum mixed colloid; S3, adding a drying control agent to the silica-alumina mixed colloid, and then stirring and standing to obtain a silica-alumina wet gel; the drying control agent is a mixture of formamide and dimethylformamide, and the mass ratio of the formamide to the dimethylformamide is 1:3 to 1:10; S4. A silica-alumina aerogel is obtained by aging, solvent replacement and segmented drying the silica-alumina wet gel.

2. The method for preparing silicon-alumina aerogel from fly ash according to claim 1, characterized in that: In step S1, the mass fraction of the sodium hydroxide aqueous solution is 15% to 30%.

3. The method for preparing silicon-alumina aerogel from fly ash according to claim 1 or 2, characterized in that: In step S1, the reaction temperature of the alkaline dissolution reaction is 60°C to 150°C, and the reaction time is 30min to 180min.

4. The method for preparing silicon-alumina aerogel from fly ash according to claim 1 or 2, characterized in that: In step S2, the CO2 is introduced at a rate of 10 ml / min to 100 ml / min.

5. The method for preparing silicon-alumina aerogel from fly ash according to claim 1 or 2, characterized in that: In step S3, the amount of the drying control agent added is 10% to 30% of the volume of the silicon-aluminum mixed colloid.

6. The method for preparing silicon-alumina aerogel from fly ash according to claim 1 or 2, characterized in that: In step S4, the aging time is 6 to 48 hours, and the aging temperature is 20° C. to 50° C.

7. The method for preparing silicon-aluminum aerogel from fly ash according to claim 1 or 2, characterized in that: In step S4, during the solvent replacement process, the replacement temperature is 20°C to 60°C, and the replacement time is preferably 4 to 10 hours.

8. The method for preparing silicon-alumina aerogel from fly ash according to claim 7, characterized in that: The solvent used for the solvent replacement is one or more of deionized water, ethanol, isopropanol, acetone, and n-hexane.

9. The method for preparing silicon-aluminum aerogel from fly ash according to claim 8, characterized in that: The volume ratio of the solvent used for the solvent replacement to the wet silica-alumina gel is 1:1 to 20:1, and the number of replacements is preferably 3 to 7 times.

10. The method for preparing silicon-alumina aerogel from fly ash according to claim 1 or 2, characterized in that: In step S4, the staged drying includes four stages of drying with a drying temperature gradually increasing within a range of 20°C to 180°C; Preferably, the drying conditions of the four-stage drying include: the temperature of the first stage drying is 20°C to 40°C, and the drying time is 12 to 48 hours; the temperature of the second stage drying is 40°C to 80°C, and the drying time is 6 to 12 hours; the temperature of the third stage drying is 80°C to 120°C, and the drying time is 2 to 4 hours; the temperature of the fourth stage drying is 120°C to 180°C, and the drying time is 0.5 to 2 hours.